Reference year proposal for the voluntary deforestation-free commitments in the Peruvian Amazon - Pozo, Patricia Luna del; Ivanova, Yovita; Coronel, Daniel; Tristán Febres, María Claudia; Muñoz, Fabiola; Quintero, Marcela (2022)
This Policy Brief presents a proposal based on an extensive review of bibliographic sources and structured interviews, as part of a study on the reference year for voluntary deforestation-free commitments in the Peruvian Amazon. Subsequently, the information has been validated through two consultation workshops with key stakeholders, including decision makers from the public and private sectors and associations representative of the cacao, oil palm, and coffee value chains, as well as civil society stakeholders. This proposal is also applicable to livestock and other agricultural value chains in the Amazon region.